Prognostic significance of elevated troponin in non-cardiac hospitalized patients: A systematic review and meta-analysis. (December 2014) - Ahmed, Amna N.; Blonde, Ken; Hackam, Daniel; Iansavichene, Alla; Mrkobrada, Marko
Abstract Cardiac biomarker troponin can be elevated in patients without a primary cardiac diagnosis and may have prognostic value. We conducted a systematic review to estimate the prevalence and prognostic significance of elevated troponin levels in patients admitted to hospital without a primary cardiac diagnosis. Literature search was done using MEDLINE (1946 to November 2012), EMBASE (1974 to Week 45, 2012), and Cochrane Central Register of Controlled Trials (November 2012). Two independent investigators reviewed full-text studies for final inclusion. We included studies of patients admitted without a primary cardiac diagnosis. Eligible studies compared adverse outcomes in patients with normal versus elevated troponin levels. Twenty-seven studies were included in the meta-analysis. Elevated troponin was associated with increased in-hospital and 30-day mortality (25 studies, 7255 patients, OR 3.88, 95% CI 2.90–5.19, P < 0.0001). Elevated troponin was also associated with increased risk of long-term mortality at 6 months (9 studies, 5368 patients, OR 4.21, 95% CI 1.84–9.64, P < 0.00001). Troponin is an independent predictor of short-term mortality with a pooled adjusted OR of 2.36, 95% CI 1.47–3.76, P < 0.0003. In conclusion, elevated troponin in non-cardiac patients is independently associated with increased mortality.